Binding agents for low-salt, low-fat, restructured beef roasts: fish surimi and beef heart or skeletal muscle - Kenney, P.B.; Kropf, Donald H.; Kastner, Curtis L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Five percent fish surimi, unwashed or washed ground beef, and washed or unwashed beef hearts were evaluated in precooked, chunked and formed, restructured beef roasts to determine if they would increase bind in low-salt (0.2% NaCl) product. An industry-like product with 1.0% NaCl and 5% unwashed ground beef was prepared, as well as a product with 0.2% NaCl and no binder. Roasts without binder were comparable in texture and integrity to those prepared with binding agents. Washing ground heart improved the sensory traits, texture measured instrumentally, and oxidative stability of the resulting products. Color was more stable for roasts containing ground heart. Roasts with 1.0% NaCl were firmer (P<.05) and had greater tensile strength (P<.05) than all other treatments. Adding salt increased binding more than adding binders, even though acceptable products could be made with minimal salt. Using binders with or without washing is not recommended, unless processors want to expand use of beef hearts.
Keywords: Beef; Restructured; Low-salt; Bind; Muscle washing